The Urban Shift of The Western: Inscriptions of Violence in Cormac McCarthy’s 'No Country for Old Men' - Gianina Roman (Linguaculture, 2011)
The aim of this paper is to analyse of the function (s) of violence in Cormac McCarthy’s novel No Country for Old Men as well as in its 2007 highly praised screen adaptation. The analysis of the use of violence in these works starts from the premises of the embedded, inherent violence of the western genre, seeking to speculate on its contemporary developments and adjustments as well as on its conflicting conventions. “Collapse” seems to be the leitmotif of the novel a s it defines both the structure and the substance of this modern western that, infused with elements of detective fiction – an unsolved crime, moral ambiguity, violence, and an action-driven narrative, epitomizes the urban shift of the genre. The paper will also briefly tackle issues connected to the conventions of the western genre so as to delineate a context for the centrality of stark violence in the modern western.